KOMUNIKASI ORANGTUA DAN ANAK (STUDI KASUS PADA KELUARGA BEDA AGAMA) - Mashfiyatul Asmaai (Fakultas Dakwah dan Komunikasi, 2019)
Communication has a very important role in every relationship, one of which is a family relationship. Both in families who live in one religion or who live with different religions. Differences in beliefs do not have such a large impact on the harmony of a family if previously the family already had a commitment to respect each other's beliefs. It is indeed more difficult to maintain harmonious relationships based on religious differences compared to relationships with one religion. But in a family, if parents already trust and respect each other in matters of religion, then parents will also give confidence to their children to choose their own religion so as not to interfere with the establishment of communication between family members. The frequency with which communication occurs frequently between parents and children affects the emotional closeness between parent and child. The more frequent communication occurs within a family, the familial relationship will be more intimate and bring about mutual openness among family members. Because of the communication style given by parents to children can have an influence on the pattern of development of children's thinking.